Primary Pericardial Synovial Sarcoma in an Adolescent Patient: Magnetic Resonance and Diffusion-weighted Imaging Features. Issue 4 (May 2015) - Ozmen, Evrim; Kayadibi, Yasemin; Samanci, Cesur; Ustundag, Nil; Ozdemir, Gulnihal; Adaletli, Ibrahim; Kurugoglu, Sebuh
Abstract : Primary synovial sarcomas of the pericardium are extremely rare tumors, especially in pediatric population. As far as we know, only few cases have been reported in the literature. This uncommon location for synovial sarcomas could lead to misdiagnosis. Radiologists and clinicians should be aware of the imaging findings and differential diagnosis of pericardial synovial sarcoma. Herein we presented a 15-year-old boy who had primary pericardial synovial sarcoma with imaging features.